Pharmacological Suppression of CNS Scarring by Deferoxamine Reduces Lesion Volume and Increases Regeneration in an In Vitro Model for Astroglial-Fibrotic Scarring and in Rat Spinal Cord Injury In Vivo - Vogelaar, Christina Francisca; König, Brigitte; Krafft, Stefanie; Estrada, Veronica; Brazda, Nicole; Ziegler, Brigida; Faissner, Andreas; Müller, Hans Werner (PLOS ONE, 2015)
Lesion-induced scarring is a major impediment for regeneration of injured axons in the central nervous system (CNS). The collagen-rich glial-fibrous scar contains numerous axon growth inhibitory factors forming a regeneration-barrier for axons. We demonstrated previously that the combination of the iron chelator 2,2’-bipyridine-5,5’-decarboxylic acid (BPY-DCA) and 8-Br-cyclic AMP (cAMP) inhibits scar formation and collagen deposition, leading to enhanced axon regeneration and partial functional recovery after spinal cord injury. While BPY-DCA is not a clinical drug, the clinically approved iron chelator deferoxamine mesylate (DFO) may be a suitable alternative for anti-scarring treatment (AST). In order to prove the scar-suppressing efficacy of DFO we modified a recently published in vitro model for CNS scarring. The model comprises a co-culture system of cerebral astrocytes and meningeal fibroblasts, which form scar-like clusters when stimulated with transforming growth factor-β (TGF-β). We studied the mechanisms of TGF-β-induced CNS scarring and compared the efficiency of different putative pharmacological scar-reducing treatments, including BPY-DCA, DFO and cAMP as well as combinations thereof. We observed modulation of TGF-β-induced scarring at the level of fibroblast proliferation and contraction as well as specific changes in the expression of extracellular matrix molecules and axon growth inhibitory proteins. The individual and combinatorial pharmacological treatments had distinct effects on the cellular and molecular aspects of in vitro scarring. DFO could be identified as a putative anti-scarring treatment for CNS trauma. We subsequently validated this by local application of DFO to a dorsal hemisection in the rat thoracic spinal cord. DFO treatment led to significant reduction of scarring, slightly increased regeneration of corticospinal tract as well as ascending CGRP-positive axons and moderately improved locomotion. We conclude that the in vitro model for CNS scarring is suitable for efficient pre-screening and identification of putative scar-suppressing agents prior to in vivo application and validation, thus saving costs, time and laboratory animals.